Woodward H. Brown letter to Nicholas S. Halmi regarding bird sightings, November 16, 1978 - Brown, Woodward H.et al (1978)
Letter from Woodward H. Brown to Nicholas S. Halmi regarding bird sightings, November 16, 1978. The Item includes a field report titled "Fall 1978, Des Moines." This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1978. Epson - sheet feed/flatbed